Beyond The School Walls: A Graduate Tracer Study of The NEUST-BSN Batch 2021-2022 - Mamaril, Agatha; Manuzon, Mary; Medrano, Avic; Mesina, Mark; Pacoma, Kimberly; Parcibigan, Ariza (Proceedings Series on Health & Medical Sciences, 2025)
Focusing on the graduates of Nueva Ecija University of Science and Technology Batch 2021-2022, this study encompassed the investigation and analysis of the post-graduation trajectories and experiences of alumni from the NEUST College of Nursing batch 2021-2022 in their employment career. Focused on understanding the career paths, employment status, further education pursuits, skills utilization, and overall outcomes of graduates that can be used as a guide to create an optimum curriculum for future students. This study used a descriptive quantitative research design to gather quantifiable data and statistically analyze a population of Nueva Ecija University of Science and Technology (NEUST) - College of Nursing batch 2021 to 2022. In this study, the researchers sought to identify the percentage of the demographic profile, skills, employability, training, advanced studies, and employment data to gain valuable feedback among nursing graduates, and it could help shape the NEUST College of Nursing's current curriculum. Overall, the NEUST-BSN batch 2021-2022 utilized communication skills, with 80.65% of respondents stating their usefulness. Additionally, 64.52% of the respondents found human relations skills valuable, while entrepreneurial skills were deemed useful by 12.90% of respondents. Information technology skills were helpful in their first job, according to 32.26% of respondents. Problem-solving skills were also found to be valuable competencies acquired in college with 62.37% respondents. Furthermore, 84.95% of respondents answered that they find critical thinking skills useful in their first job. Data analysis reveals that the majority of the graduates are employed and have found their jobs aligned with their undergraduate studies. The graduates also place a high priority on ongoing professional growth through additional education and training.